Leishmania infantum amastigotes enhance HIV-1 production in cocultures of human dendritic cells and CD4 T cells by inducing secretion of IL-6 and TNF-alpha. - Ravendra Garg; Corinne Barat; Michel Ouellet; Robert Lodge; Michel J Tremblay (Public Library of Science (PLoS), 2009)
Visceral leishmaniasis has emerged as an important opportunistic disease among patients infected with HIV-1. Both HIV-1 and the protozoan parasite Leishmania can productively infect cells of the macrophage-dendritic cell lineage.Here we demonstrate that Leishmania infantum amastigotes increase HIV-1 production when human primary dendritic cells (DCs) are cocultured together with autologous CD4(+) T cells. Interestingly, the promastigote form of the parasite does not modulate virus replication. Moreover, we report that amastigotes promote virus replication in both cell types. Our results indicate that this process is due to secretion of parasite-induced soluble factors by DCs. Luminex micro-beads array system analyses indicate that Leishmania infantum amastigotes induce a higher secretion of several cytokines (i.e. IL-1alpha, IL-2, IL-6, IL-10 and TNF-alpha) and chemokines (i.e. MIP-1alpha, MIP-1beta and RANTES) in these cells. Studies conducted with pentoxifylline and neutralizing antibodies revealed that the Leishmania-dependent augmentation in HIV-1 replication is due to a higher secretion of IL-6 and TNF-alpha.Altogether these findings suggest that the presence of Leishmania within DC/T-cell conjugates leads to an enhancement of virus production and demonstrate that HIV-1 and Leishmania can establish complex interactions in such a cellular microenvironment.